Rus devrimi etkisinde gelişen avangard-sanat ve görsel tasarım - Özkurt, Cem (My University, 2006)
Bölüm 1. RUS DEVRÜMÜ ETKÜSÜNDE ÜLK AVANTGARD YAKLAŞIMLAR Sanat alanında her yeni deney teknik ve mühendislikten dolar, bunun da baßÝnÝ organizasyon ve inßa eker. Biliyoruz ki tat ve zevk duyularÝ sonsuza dek šldŸ. Alexander Rodchenko (1921) ‚oktan tamamlanmÝß olan evrensel bir sistemin par asÝ olan SŸprematizm, bizim i in mŸkemmel formun tanÝmÝnÝ ißaret etmez. Tersinden burada ilk kez tŸm a ÝklÝÛÝ ve saflÝÛÝyla ißaret veren ve daha šnce hi denenmemiß yeni bir dŸnyanÝn kesin planÝ, karßÝmÝzda ortaya ÝkmÝßtÝr - bu dŸnya, i sel varlÝÛÝmÝzÝ ve sadece daha ilk basamakta kendi formasyonunu dÝßarÝ yayar. Bu yŸzden sŸprematizm emberi bir ißaret ateßi olarak bilinmeye baßlamÝßtÝr. El Lissitzky (1920) SanatÝn sanat olarak bir ger eÛi ifade ettiÛi gšrŸlŸr, bir deneyimdir, radikal praksis alanÝnda olmamasÝna raÛmen bir gereklilik olmasÝyla birlikte devrimin olmazsa olmaz yapÝ taßÝdÝr. Herbert Marcuse (1978) BšlŸm 2. AVRUPALI SANAT‚ILARIN, DEVRÜM D…NEMÜ RUS AVANGARD'IYLA ve RUS SANAT‚ILARLA ETKÜLEÞÜMÜ SÝnÝf mŸcadelesinin gerekliÛi ve durumuyla bŸtŸnleßmiß olan bizler, bir insanÝn bir resimden, bir ßiirden ya da mŸzikten keyif almasÝnÝ šnemli bulmuyoruz. …nceliÛimiz, insanlÝÛÝn modern standardÝna ulaßmamÝß olanlarÝn, alÝßmalarÝmÝz sayesinde bir an šnce bu a ÝklarÝnÝ kapatmalarÝnÝ saÛlamaktÝr. Laszlo Moholy-Nagy (1922) ‚ok yaratÝcÝ bir sŸrecin baßlangÝcÝndayÝz. GšrŸldŸÛŸ Ÿzere, burjuva inadÝ ve diÛer tepkiler, Avrupa'nÝn her tarafÝnda olduÛu kadar ißlerin karÝßÝk olduÛu Rusya'da da yoÛun. Fakat ge miße baÛlÝ kalmaya alÝßanlarÝn enerjisi, yeni varoluß bi imleri ve ortak alÝßma alanlarÝ yaratma sŸrecini geciktirmekten fazlasÝnÝ yapamayacaktÝr. El Lissitzky ve Ilya Ehrenburg (1922) Ne yazÝk ki yapÝsalcÝlar pratikte yetersizler ama larÝnÝ ger ekleßtiremiyorlar. ‚oÛunlukla, sanatÝn geleneksel kalÝplarÝnÝ kÝramÝyorlar. UnuttuklarÝ ßey, tek bir tip yapÝsalcÝ olduÛu kuralÝ: mŸhendis, mimar, kaynak Ý, marangoz. Tek kelimeyle teknisyen. Lider olmak i in yola ÝkmÝßlardÝ fakat belli oluyor ki yalnÝzca bir refleks olabilmißler. George Grosz (1925) BšlŸm 3 . YAPISALCI TASARIM PRATÜÚÜ VE G…RSEL TASARIM †R†NLERÜ Tsarist Rusya'da šrneÛi bulunmayan artist-constructor'un yeni bir tipini yaratmak olduk a zor bir hedefti. Alexander Rodchenko Ben ve bŸtŸn grup i in, aÛdaßlÝÛÝ anlamamÝzÝ yaratÝcÝ ve somut bir ßekilde šÛreten adam Profesšr Radchenko'dur. Production art'daki yeni yerimizi gšsterdi ve ortaya ÝkardÝ. Gelißmiß fikirleri ve pek ok alandaki yaratÝcÝlÝÛÝyla, bize ok ßeyler šÛretti. Zakhar Nikolaevic Bykov BÝrakÝn sokaktaki adam iÛrenerek Rodchenko'nun yapÝlarÝnÝn demirden yapÝm gŸcŸne tŸkŸrsŸn. Osip Brik (1923) 4 . DEVRÜM RUSYA'SINDA S†RELÜ YAYIN TASARIMI: USSR in Construction Sanayileßmeden sosyalizme giden yolda tam hÝzla ilerlemekteyiz, eskiden beri var olan Rus geriliÛini arkamÝzda bÝrakarak...Motorlu bir arabaya USSR damgasÝnÝ bastÝÛÝmÝzda ve bir kšylŸyŸ traktšre oturttuÛumuzda o zaman hangi Ÿlkelerin geri, hangilerinin ileri olarak sÝnÝflandÝrÝldÝÛÝnÝ gšreceÛiz. Joseph Stalin (1929) Bizim kußaÛÝmÝz heyetle tam bir uyum i inde alÝßmayÝ hedefledi. Fakat deneyimler gšsteriyor ki sanatsal deÛere sahip alÝßmalar sadece sanat Ý hedefini kendisi belirlediÛi zaman yaratÝlabilir. El Lissitzky (1941) Editšrlerin verdiÛi bŸtŸn gšrevleri kabul ettiÛimiz i in biz fotomuhabirleriher zaman bireyselliÛimizi yitirme tehlikesi i indeyiz. Ünsan kendi sorunlarÝnÝ meydana koymalÝ ve kendi olanaklarÝnÝ sÝnamalÝdÝr. Alexander Rodchenko

Chapter 1. FIRST AVANT-GARDE APPROACHES UNDER THE INFLUENCE OF RUSSIAN REVOLUTION Every new experiment in the field of art has come out of technique and engineering is headed in the direction of organization and construction.We know that taste and pleasant sessations are dead for ever. Alexander Rodchenko (1921) For us SUPREMATISM did not signify the recognition of an absolute form which was part of an already-completed universal system. On the contrary here stood revealed for the first time in all its purity the clear sign and plan for a definite new world never before experienced -- a world which issues forth from our inner being and which is only now in the first stage of its formation. For this reason the square of suprematism became known as a beacon. El Lissitzky (1920) It seems that art as art expresses a truth, an experience, a necessity which, although not in the domain of radical praxis, are nevertheless essential components of revolution. Herbert Marcuse (1978) Chapter 3 . THE MUTUAL INSPIRATION BETWEEN EUROPEAN ARTISTS AND BOTH RUSSIAN AVANT-GARDES AND ARTISTS We, who today have become one with the necessity and condition of class strugle in all respects, do not think it important that a person should find enjoyment in a picture, in music, or in poetry. The primary requirement is that those who have not yet reached the contemporary standart of mankind should be enabled to do so as soon as possible through our work. Laszlo Moholy-Nagy (1922) We stand at the outset of a great creative period. Obviously reaction and bourgeois obstinacy remain strong on all sides in Europe as well as in disoriented Russia. But all the energy of those who cling to the past can only, at the very most, delay the process of cunstructing new forms of existance and communal work. El Lissitzky ve Ilya Ehrenburg (1922) Unfortunately the Constructivists have a partical failing--they're falling short of their goal. In most cases they are still confined within the traditional sphere of art. They forget that, as a rule, there is only one type of constructivist: the engineer, the architect, the welder, the carpenter. In a world, the technician. They set out to be leaders -- but were, it turns out, only a reflex. George Grosz (1925) Chapter 3 . CONSTRUCTIVIST DESIGN PRACTICE AND VISUAL DESIGN PRODUCTS The creation of a new type of artist - constructor who had no precedent in Tsarist Russia was an extremely difficult objective. Alexander Rodchenko For me and all the group, Professor Rodchenko was the man who taught us to understand the contemporary situation in a creative and concrete way. He indicated and revealed anew our place in production art. As a man with advanced ideas and creative ability in many fields, he taught us a lot. Zakhar Nikolaevic Bykov Let the man in the street spit with disgust at the iron constructive power of Rodchenko's construction. Osip Brik (1923) Chapter 4 . PERIODICAL PUBLICATION DESIGN IN THE RUSSIAN REVOLUTION PERIOD We are advancing full steam ahead along the path of industrialization to socialism, leaving behind the age-long 'Russian' backwardness... when we put the USSR in a motor car and the muzhik upon a tractor... we shall see which countries may then be classified as backward and which as advanced. Joseph Stalin (1929) Our generation has set itself the aim of working precisely in accordance with commission. But practise has shown that the work of true artistic worth can be created only when the artist sets his own objective (the internal social commission). El Lissitzky (1941) We photoreporters are always in danger of loosing our individuality because we accept all assignments from the editors. One must set forth his own problems and test his own possibilities. Alexander Rodchenko
Keywords: Avangard (Estetik)